A module configuration and valuation model for operational flexibility in ship design using contract scenarios. (17th November 2017) - Choi, Minjoo; Erikstad, Stein Ove
ABSTRACT: Modularity allows for affordable reconfiguration in operation. Thus, a single modular ship has flexibility and stakeholders have the option to delay investment decisions until more information and technology become available. However, previous design methods for modular ships have not considered the economic benefits of such operational flexibility. We therefore present an optimization model that involves both design and operation decisions related to modules. In creating design alternatives, we use component swapping modularity, in which designs are created by configuring modules to a main body through non-identical interfaces. In evaluation, we represent an operating context based on a set of contracts. We implemented the model in a case study in which both modular and non-modular ships were designed, evaluated, and compared. Moreover, a sensitivity analysis was performed for different contract scenarios. The case study shows that reconfiguration options are influential factors on the value robustness of ships under high uncertainty.